Analisis Efektivitas Thermal Insulation pada Sekat Ruang (Bulkhead) Bus untuk Mengurangi Panas Mesin - Hidayat, Muhamad Fikri; Muchlisinalahuddin, Muchlisinalahuddin; Aprilman, Devia; Adriansyah, Adriansyah; Fajri Arsyah, Ahmad Hasnul; Kamil, Muhammad Aslam (Jurnal Teknik Mesin, 2025)
This study aims to evaluate the effectiveness of two types of thermal insulation materials, namely polyurethane (PU) foam and basaltwool, in reducing heat transfer from the engine compartment to the passenger cabin through the bus bulkhead structure. Optimal thermal insulation is essential to maintain cabin thermal comfort and enhance safety within the vehicle interior. The testing methods included measurements of thermal conductivity and evaluations of each material’s resistance to extreme temperatures. The results indicate that PU foam exhibits lower thermal conductivity (±0.020–0.028 W/m·K) and achieves heat retention efficiency of 95–98% at temperatures around 100°C. On the other hand, basaltwool shows slightly higher thermal conductivity (±0.035–0.040 W/m·K) with efficiency ranging from 90–95%, but significantly outperforms in terms of heat resistance, withstanding temperatures as high as 600–1000°C. Based on these findings, PU foam is considered more suitable for applications that require thermal efficiency at moderate temperatures, while basaltwool is better suited for environments exposed to continuous high temperatures. Therefore, the appropriate selection of insulation material should be based on specific operational conditions to optimize both thermal comfort and cabin safety.